Life Cycle Assessment of Hybrid-Electric Aircraft Technologies—A Review - Aleksandra Zieminska-Stolarska; Mariia Sobulska; Daniel Izquierdo; Deborah Neumann Dela Cruz; Monika Pietrzak; Ireneusz Zbicinski (IEEE Access)
Decarbonizing aviation is a critical goal for mitigating climate change, as the sector contributes significantly to global greenhouse gas emissions. Hybrid electric aircraft (HEA) represent a promising step towards reducing the environmental impact of aviation. The paper presents a review of life cycle assessment analysis of hybrid electric aircraft designs as emerging technologies. The literature review is complemented by a presentation of the technologies developed within the HECATE (Hybrid Electric Regional Aircraft Distribution Technologies) EU project. Results of HECATE prove that for the HEA platforms, requirement for higher voltage and higher power distribution components is essential to reduce the environmental load. All the literature findings show that hybrid-electric aircraft configurations can reduce the carbon intensity per RPK (revenue passenger kilometer) from 49%-57% in the conservative scenario to 82%-88% in the best scenario when compared to fossil-fueled aircraft. The environmental impact of HEA could be further reduced by 7% if electricity for batteries charging is produced from renewable sources and battery has longer lifetime. LCA analysis shows that the main contributors to the environmental load produced by HEA are aircraft airframes and batteries, producing on average 15-40 kg CO2 eq./h.